Concept of Education in Islam and the role of Madrassah: Short History of Madrassah and Militancy in Pakistan - Ahmed, Naseem (Technium Social Sciences Journal, 2021)
Islam has given especial emphases on religious and rational education, it is obligatory to every Muslim to get education. The place where education is given to Muslims has given very especial status and respect. The Islamic education center called Madrassah; its history is as old as the Islam. Madrassah provides free education, boarding and lodging to the poor students. South Asian Madrassah traditions go back to the Muslim Rule in India, there were two famous traditions of Islamic education system in India Frangi Mahall tradition and Deobandi tradition respectively. After partition of India, Pakistan inherited both the traditions but the Deoband Tradition is stronger in theory and practice in present day Pakistan. After 9/11attaccks on United Sates of America, the world has become interested to know about Madrassahs in Pakistan and its connections with militancy. Suddenly, the media and governments have also given attention to understand the Madrassah. Several studies have been conducted by journalists, NGO’s and academia on Madrassah curriculum, policy, ideology, student-teacher relationship and connection to militancy. The main purpose of this article is to discuss the Islamic concept of education and the role of Madrassah in Islamic and rational education and to analyze the Madrassah connections with jihad and militancy. It also discusses the short history of Madrassah in India and Pakistan. In the light of the following questions what is an Islamic concept of education and the role of Madrassah? And, to analize If there is any connection of Madrassah and militancy? Key words: Islam, Education, Madrassah, Militancy and Pakistan.